Social Networking through Globalization of Education – A Survey to Students of Madras Christian College - Amuthan., V. Arockia (IJRDO -Journal of Computer Science Engineering, 2015)
Technology plays a significant role in classroom transformation. The internet is called as connecting to knowledge. The system of education has also adopt digital age of teaching method. This study focused how facebook play vital role of marketing to commodities and how to use for our education system in the competitive world. To examine the effective usage of Facebook, a popular online social network site in India, as marketing media among to the students of Madras Christian College. Marketing strategies that once included careful message development broadcast to mass audiences, are now giving way to the idea that the public is a co-creator of brand messages and a trustworthy promotion channel. The online social network application analyzed in this article, Facebook, enables its users to present themselves in an online profile, accumulate “friends” who can post comments on each other’s pages, and view each other’s profiles. Facebook members can also join virtual groups based on common interests, see what classes they have in common, and learn each others’ hobbies, interests, musical tastes and romantic relationship status through the profiles. Facebook is a social networking service and website launched in February 2004, owned and operated by Facebook, Inc. As of May 2012, Facebook has over 900 million active users, more than half of them using Facebook on a mobile device. Facebook allows any users who declare them to be at least 13 years old to become registered users of the site. The main objective of this present study is broadly analyse to how Facebook help to increase brand value for various goods and services and marketing tools of students community